Cluster of Differentiation 24 Expression Is an Independent Prognostic Factor of Adverse Outcome in Cervical Carcinoma. Issue 2 (1st February 2013) - Huang, Lee-Wen; Lee, Chin-Cheng
Abstract : Objective: Cluster of differentiation (CD) 24 is a cell adhesion molecule that has been implicated in tumor invasion and metastasis of various solid tumors. The aim of this study was to explore the expression patterns of CD24 as a predictive marker for long-term survival in cervical carcinomas. Methods: A total of 144 patients diagnosed with International Federation of Gynecology and Obstetrics stage I to IV cervical carcinoma were studied, and 95 patients underwent surgical intervention. The expression of CD24 protein was studied by immunohistochemistry using tissue microarrays. Results: Overexpression of CD24 was observed in 50 (34.7%) of 144 invasive carcinomas. Patients with CD24 overexpression had poorer survival compared with that of patients with CD24 underexpression (5-year survival rate, 52.0% vs 72.3%; log rank P = 0.014). Importantly, in multivariate analysis, CD24 overexpression proved to be a significant independent predictor of short-term survival (relative risk, 1.814; P = 0.043). Conclusions: The present study suggests that CD24 overexpression is a predictor of decreased long-term survival in patients with cervical carcinoma. Therefore, immunohistochemical evaluation of CD24 expression is a potential prognostic biomarker for cervical carcinomas.